Mental health and psychosocial well-being of Ukrainian social work students affected by Russia’s full-scale invasion - Yaser Snoubar (14634232) (2025)
This study explores the mental health and psychosocial well-being of Ukrainian social work students after Russia’s full-scale invasion. The primary aim is to assess the levels of anxiety, depression, and stress among these students, alongside their perceived social support and quality of life, to understand the implications for their mental health and psychosocial well-being. Utilizing a cross-sectional design, the survey questionnaire was administered to 168 Ukrainian social work students. The findings reveal significantly high levels of anxiety, depression, and stress. Variations in perceived social support were observed, with those in marital relationships reporting higher levels of support. Predictive regression analysis identified key predictors of mental health outcomes, including the impacts of quality of life and academic difficulties. The results emphasize the urgent need to enhance mental health support within educational settings and to develop interventions tailored to the unique challenges faced by social work students in conflict zones. These findings carry profound implications for social work policy and practice, highlighting the critical need for robust support systems and specialized training to prepare future social workers to effectively support populations affected by wars. Other Information Published in: The British Journal of Social Work License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/bjsw/bcaf079